2014
DOI: 10.1080/1745039x.2014.950451
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mild heat stress on dry matter intake, milk yield and milk composition in mid-lactation Holstein dairy cows in a temperate climate

Abstract: The aim of the present study was to evaluate the impact of summer temperatures in a temperate climate on mid-lactation Holstein dairy cows. Therefore, a data set was examined comprising five trials with dairy cows conducted at the experimental station of the Friedrich-Loeffler-Institute in Braunschweig, Germany. The temperature-humidity index (THI) was calculated using temperature and humidity data from the barns recorded between January 2010 and July 2012. By using a generalised additive mixed model, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 26 publications
4
55
1
5
Order By: Relevance
“…Links between production and heat stress have been demonstrated previously [16]. Both the consumption of dry matter (DM) and milk production decrease when the temperature humidity index (THI) was >60 [17]. Furthermore, water consumption increases linearly under mild heat stress when THI exceeds 30 [17] and hence daily water use fluctuations are typically greater in summer months [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Links between production and heat stress have been demonstrated previously [16]. Both the consumption of dry matter (DM) and milk production decrease when the temperature humidity index (THI) was >60 [17]. Furthermore, water consumption increases linearly under mild heat stress when THI exceeds 30 [17] and hence daily water use fluctuations are typically greater in summer months [18].…”
Section: Introductionmentioning
confidence: 99%
“…Both the consumption of dry matter (DM) and milk production decrease when the temperature humidity index (THI) was >60 [17]. Furthermore, water consumption increases linearly under mild heat stress when THI exceeds 30 [17] and hence daily water use fluctuations are typically greater in summer months [18]. Heat stress mitigation, such as cow showers, can decrease cow body temperature by 0.2 • C and showered cows spend half as much time near water bowls [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to Gorniak et al (2), even mild heat stress in cows kept in a temperate climate negatively affects milk production. Moreover, the decline in performance they observed could not be explained solely by reduced feed intake, and other factors, including changes in energy metabolism, might have contributed to decreased milk yield (2). At the physiological level, a hot environment was shown to induce several adaptive responses, including alterations of lipid metabolism (3).…”
mentioning
confidence: 99%
“…The negative influence of elevated environmental temperatures on economically important traits is well recognized in cattle. Thermal stress is responsible for decreased milk yield, milk fat, and protein contents, as well as reduced dry matter intake, health, and fertility (1,2). According to Gorniak et al (2), even mild heat stress in cows kept in a temperate climate negatively affects milk production.…”
mentioning
confidence: 99%
“…Even though the physiological mechanisms are unclear, it is believed that these metabolic modifications under heat stress during lactation account for approximately 50% of the milk production loss observed (6), whereas decreased dry matter intake (DMI) explains the remainder of the depressed milk yield (16). Also, it was found that the stage of lactation has a negative influence on milk production under the environmental condition of heat stress (17).…”
Section: Discussionmentioning
confidence: 99%